Síntese de ciclodextrinas pentafluorpropioniladas e suas aplicações como fases estacionárias quirais em cromatografia gasosa enantiosseletiva - Mallmann, Anderson Stoffels (2008)
Three new α, β- and γ-cyclodextrins derivatives were synthesized: hexakis-(2,6-di-O-pentyl)-α-cyclodextrin, heptakis-(2,6-di-O-pentyl)-β-cyclodextrin and octakis-(2,6-di-O-pentyl)-γ-cyclodextrin. The structures were elucidated using Nuclear Magnetic Resonance techniques such 1H, 13C, COSY 1H-1H and HMQC. Three new chiral chromatographic columns were prepared with the obtained chiral phases and the achiral phase OV 1701. All the columns were tested with various racemic compounds, showing efficiency in their chiral resolution such as: alcohols, acetylated alcohols, trifluoroacetylated alcohols, aminoacids, organic acids esters, monoterpenic hydrocarbons, ketones, lactones, drugs, sulphur compounds, selenium compounds and halogenated compounds. The column confeccionated with the stationary phase 2,6-Pe-3-PFP-α-CD/OV 1701 (1:1) showed better results on the separation of (+/-)-menthol-OAc and (+/-)-borneol. Many compounds were tested and separated by the chiral column 2,6-Pe-3-PFP-β-CD/ OV 1701 (1:1). Good results were obtained on the stereoselective separation of (+/-)-2-decanol-O-Ac, (+/-)-2-decanol-O-TFA, (+/-)-2-undecanol-O-Ac,(+/-)-2-undecanol-O-TFA, (+/-)-phenylethanol-O-Ac, (+/-)-phenylpropanol-O-Ac, (+/-)- borneol-O-Ac, (+/-)-borneol-O-TFA, (+/-)-menthol-O-Ac, (+/-)-2-phenyl-2-butanol-OAc, (+/-)-2-phenyl-2-pentanol-O-Ac, D,L-alanine-O-ethyl, R,S-(E)-ethyl-2-(4-oxopent- 2-en-2-ilamino)propanoate, (+/-)-2,3- bromopropionic acid, (+/-)-mandelic acid, (+/-)-α - pinene, (+/-)-camphor, (+/-)-carvone, (+/-)-α-ionone, (+/-)-amphetamine, (+/-)-cyclohexyl benzenesulfinate, (+/-)-1-(ethylsulfinyl)benzene, (+/-)-1- (methylsulfinyl)benzene, (+/-)-1-(methylsulfinyl)-4-methyl benzene and (+/-)-1- (ethylsulfinyl)-4-methyl benzene. The columns with 2,6-Pe-3-PFP-γ-CD/ OV 1701 (1:1) showed good results on the separations of (+/-)-borneol, (+/-)-borneol-O-Ac, (+/-)-borneol-O-TFA, (+/-)-neo-menthol, (+/-)-menthol-O-Ac, (+/-)-2-decanol-O-Ac, (+/-)-2-undecanol-O-Ac, D,L-leucine, (+/-)-β-hydroxy-leucine, (+/-)-α-pinene, (+/-)-camphor, (+/-)-carvone and (+/-)-α-ionone.